2019
DOI: 10.1016/j.parkreldis.2019.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment of behavioral and cognitive symptoms of Parkinson's disease

Abstract: Cognitive and behavioral symptoms are common in Parkinson's disease, may occur even in the prodromal stages of the disease, worsen with disease progression, and surpass motor symptoms as the major factors affecting patient quality of life and caregiver burden. The symptoms may be caused by the disease pathology or they may represent adverse effects of treatment, or both etiological factors may contribute. Although many of these symptoms are related to dopaminergic dysfunction or dopaminergic medication, other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 177 publications
(204 reference statements)
0
14
0
6
Order By: Relevance
“…3 Recent studies suggest that the progressive disability, patient's mood, speech difficulties, and cognitive deterioration are the main factors contributing to caregiver burden and poorer caregiver's QoL. [4][5][6][7][8][9] Most PD patients are cared for in their own homes and spouses are the main informal caregivers. 10,11 During the disease progression, the caregiver of a PD patient assumes many responsibilities, including medication administration, care coordination, prompting for selfcare, surveillance of falls, provisions of emotional support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Recent studies suggest that the progressive disability, patient's mood, speech difficulties, and cognitive deterioration are the main factors contributing to caregiver burden and poorer caregiver's QoL. [4][5][6][7][8][9] Most PD patients are cared for in their own homes and spouses are the main informal caregivers. 10,11 During the disease progression, the caregiver of a PD patient assumes many responsibilities, including medication administration, care coordination, prompting for selfcare, surveillance of falls, provisions of emotional support.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Recent studies suggest that the progressive disability, patient’s mood, speech difficulties, and cognitive deterioration are the main factors contributing to caregiver burden and poorer caregiver’s QoL. 4 9 Most PD patients are cared for in their own homes and spouses are the main informal caregivers. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…Os sintomas não motores da DP costumam preceder os motores em até 10 anos, sendo comum o aparecimento de anedonia, apatia, disgeusia, fadiga, dor, disfunções do comportamento no sono REM, hiposmia, disfunção autonômica, alterações visuais e depressão (SVEINBJORNSDOTTIR, 2016). As opções de tratamento atualmente disponíveis para os sintomas não motores comportamentais e cognitivos são, em geral, menos bem-sucedidas na compensação dos sintomas a longo prazo do que as opções de tratamento para os sintomas motores (REKTOROVA, 2019).…”
Section: Fundamentação Teóricaunclassified
“…In another recent review, dopamine agonists (piribedil, rotigotine and pramipexole) have been reported to improve levels of apathy in PD (Rektorova, 2019).…”
Section: Other Disordersmentioning
confidence: 99%